Optimization of process parameters using response surface methodology (RSM) for power generation via electrooxidation of glycerol in T-Shaped air breathing microfluidic fuel cell (MFC) - Panjiara D.; Pramanik H. (My University, 2025)
The present work focuses on the optimization of operating parameters using Box Behnken design (BBD) in RSM to obtain maximum power density from a glycerol based air-breathing T-shaped MFC. The major parameters influencing the experiment for enhancing the cell performance in MFC are glycerol/fuel concentration, anode electrolyte/KOH concentration, anode electrocatalyst loading and cathode electrolyte/KOH concentration. The ambient oxygen is used as the oxidant. The acetylene black carbon (CAB) supported laboratory synthesized electrocatalyst Pd–Pt (16:4)/CAB is used as anode electrocatalyst and commercial Pt (40 wt%)/CHSA as the cathode electrocatalyst. The quadratic model predicts the appropriate operating conditions to achieve highest power density from the laboratory designed T-shaped MFC. The p-value of less than 0.0001 and F-value of greater than 1 i.e., 26.32 indicate that the model is significant. The optimum conditions predicted by the RSM model were glycerol concentration of 1.07 M, anode electrolyte concentration of 1.62 M anode electrocatalyst loading of 1.12 mg/cm2 and cathode electrolyte concentration of 0.69 M. The negligible deviation of only 1.07% between actual/experimental power density (2.76 mW/cm2) and predicted power density (2.79 mW/cm2) was recorded. This model reasonably predicts the optimum conditions using Pd–Pt (16:4)/CAB electrocatalyst to obtain maximum power density from glycerol based MFC. © 2020 Hydrogen Energy Publications LLC